Aflatoxin M1 occurrence in Serbian milk and its impact on legislative - Jajić, I.; Glamočić, D.; Krstović, S.; Polovinski Horvatović, M. (Journal of the Hellenic Veterinary Medical Society, 2019)
Serbia is a country which has repeatedly changed aflatoxin M1 (AFM1) legislation in milk. As a country that clearly has aspiration toward the EU membership, Serbia implemented the EU legislation for this mycotoxin at level of 0.050 μg/kg. However, due to high occurrence of AFM1 in milk, legislation has been changed several times in the past few years as an effort to preserve domestic milk production. This paper presents the results of four years monitoring of different milk types taken from Serbian market and from Serbian farmers. The samples were analyzed by liquid chromatography on ODS Hypersil column with fluorescence detector (FLD), after cleanup on immunoaffinity column. Limit of quantification was 0.005 μg/kg, while obtained mean value for trueness was 95.1%, respectively. Average AFM1 levels in 2013, 2014, 2015 and 2016 were 0.205, 0.127, 0.238. and 0.269 μg/kg, respectively. Overall occurrence of AFM1 was 80.9%, with the average content of 0.216 μg/kg (ranged from 0.005 to 5.078 μg/kg). According to this, 49.1% of samples were above the EU regulation. In years to come, Serbia will have a challenge to produce the milk that is in compliance with the permitted level of AFM1. Especially, when it is known that in not so distant future, an increase in temperature as a result of the certain climate changes is expected.